IMPLEMENTATION OF VPN SERVER USING L2TP PROTOCOL AND IPSEC METHODS AS NETWORK SECURITY - Ruri Hartika Zain; Retno Devita; Ipriadi -; Ondra Eka Putra (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
This study aims to design a VPN network system by utilizing a public network, where this system aims to provide security by using IPSec in providing confidential information through the L2TP tunnel method from the server to the branch/client computer and vice versa. VPN is implemented using layer 2 tunneling protocol (L2TP) using two Mikrotik routers. There are only a few changes in the computer network configuration to minimize costs and implementation time. Tests are carried out to implement security on the network using the command prompt, where the admin observes packet loss and delay parameters to find out the increase in security quality on the network